Physical quality and in vitro starch digestibility of biscuits as affected by addition of soluble dietary fiber from defatted rice bran. (February 2020) - Jia, Mengyun; Yu, Qiang; Chen, Jiajun; He, Zhicheng; Chen, Yi; Xie, Jianhua; Nie, Shaoping; Xie, Mingyong
Abstract: The increasing demand for functional foods has boosted up the food industry to produce fiber-enriched products. The purpose of this study was to investigate the effects of soluble dietary fiber from defatted rice bran (DRB) obtained through Trichoderma viride fermentation (F-SDF) on the physical properties and starch digestion characteristics of biscuits. Rheological analysis results showed that the addition of F-SDF delayed the gelatinization of starch. Texture profile analysis (TPA) results demonstrated that the addition of F-SDF reduced the hardness, springiness, cohesiveness, gumminess, chewiness and resilience of the biscuits. The scanning electron microscopy (SEM) results showed that F-SDF hindered the formation of the gluten network structure in the biscuits, making the biscuits loose. Meanwhile, X-ray diffraction (XRD) revealed the addition of F-SDF reduced the area of the crystallization zone. In addition, F-SDF led to a significant reduction of predicted glycemic index ( pGI ) of reformulated biscuits. Sensory evaluation results indicated that the effects of F-SDF addition on the odor, color and taste of the biscuits were relatively small, while the biscuits with highest texture and acceptability score were obtained by incorporating 6% of F-SDF in the formulation. In summary, adding the proper amount of F-SDF could improve the physical properties of the biscuits and exhibit potential to decrease the postprandial blood glucose level resulted by biscuits. Graphical abstract: Image 1 Highlights: ● F-SDF from defatted rice bran hindered the gelatinization of starch in doughs. ● Texture, microstructure, crystallinity of biscuits were affected by F-SDF addition. ● F-SDF led to a reduction in the expected glycemic index of reformulated biscuits. ● The effects of F-SDF on the odor, color and taste of the biscuits were small. ● Highest texture and acceptability score were obtained by addition of 6% F-SDF.